2000
DOI: 10.1164/ajrccm.162.4.9908104
|View full text |Cite
|
Sign up to set email alerts
|

Commercial versus Native Surfactants

Abstract: Despite their broad clinical use, there is no standardized comparative study on the functional, biochemical, and morphologic differences of the various commercial surfactants in relation to native surfactant. We investigated these parameters in Alveofact, Curosurf, Exosurf, and Survanta, and compared them with native bovine (NBS) and porcine (NPS) surfactant. For Curosurf and Alveofact the concentrations necessary for minimal surface tensions < 5 mN/m were six to 12 times higher (1.5 and 3 mg/ml, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 44 publications
2
131
0
2
Order By: Relevance
“…The overall compositions of the lipid extracts of BAL and extracts from minced lungs extracts are similar with only small differences in phospholipid composition (56). The hydrophilic proteins (SP-A and SP-D) are not present in any of the two extract types due to the low solubility in the organic solvents.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The overall compositions of the lipid extracts of BAL and extracts from minced lungs extracts are similar with only small differences in phospholipid composition (56). The hydrophilic proteins (SP-A and SP-D) are not present in any of the two extract types due to the low solubility in the organic solvents.…”
Section: Resultsmentioning
confidence: 86%
“…The surfactant is extracted from minced porcine lungs by the method of Bligh and Dyer (55). After extraction only the hydrophobic surfactant proteins (SP-B and SP-C) are present in the LSE, at a concentration of 1 to 2% each, with complete removal of the hydrophilic surfactant proteins (56,61). The 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), POPC, 1,2-dipalmitoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (DPPG), and cholesterol were purchased from Avanti Polar Lipids.…”
Section: Methodsmentioning
confidence: 99%
“…It is found that all three proteins promote fusion of the unilamellar micelles into larger multilamellar micelles, in good agreement with experimental observations of the ultrastructure of protein-containing natural PS. 15,34 Specifically, it is found that the hydrophobic SP-B (in orange) and SP-C (in purple) mainly assume transmembrane positions, whereas the hydrophilic SP-A (in violet) locates primarily at the intermembrane space to bridge individual micelles. In general, results of our MD simulations are in good agreement with the current molecular understanding and predication of lipid− protein interactions in natural PS vesicles and films.…”
Section: Resultsmentioning
confidence: 99%
“…Alveofact (Boehringer Ingelheim, Ingelheim am Rhein, Germany) is an organic solvent extract of a fraction isolated from cow lung lavage. It contains 88% phospholipids, 4% cholesterol, 8% other lipids and 1% hydrophobic proteins (SP-B, SP-C) [17]. In addition, a synthetic surfactant preparation (Venticute; Nycomed Deutschland GmbH, formerly Altana Pharma AG) was used which is well characterized and consists of 63.4% 2-dipalmitoyl-sn-glycero-3-phosphocholine, 27.8% 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol, 4.5% palmitic acid, 2.5% calcium chloride and 1.8% recombinant SP-C (lusupultide) [18].…”
Section: Methodsmentioning
confidence: 99%